Systematic Literature Review Analysis Dividend Policy in the Era of Covid-19 Pandemic - Reski Putra Utama; Wisudanto Wisudanto (Jurnal Mantik, 2023)
This article presents a systematic literature review using qualitative content analysis, we found that during crisis conditions caused by the COVID-19 pandemic, corporate companies tend to increase dividend payouts compared to the previous year, with the aim of maintaining positive signals to the stock market. There are several factors that influence dividend policy. Factors such as profitability, firm age, and financial leverage have a positive influence on dividend policy, while firm size has a negative influence. In addition, dividend policy is also positively influenced by the previous year's dividend and the level of dividend payments in the previous period.